2014
DOI: 10.4028/www.scientific.net/msf.792.379
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Magnet Arrangements in Double Layer Interior Synchronous Permanent Magnet Motor over Wide-Speed Range for Electric Vehicle Applications

Abstract: In this paper, the magnet arrangement for a manufactured Double Layer Interior Synchronous Permanent Magnet Motor (DLISPMM) for Electric Vehicle (EV) applications is investigated. In a first step, the manufactured motor is optimized for its nominal condition, by using a particular design of experiment (DOE) method. In a second step, a comparative analysis for the two types of DLISPMMs for a wide speed range operation is performed, by using a parametric Finite Element (FE) model, for calculation of the main mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The Interior Permanent Magnet Synchronous Motors (IPMSMs) are considered to be an advantageous option for EV applications, due to their superior nominal characteristics, including high efficiency, torque density, fault tolerant capability and a wide speed operating range [1]- [3]. Double Layer IPMSMs are highly adopted for EV applications, due to their high saliency ratio and low induced Permanent Magnet (PM) flux, enhancing their suitability for high speed operating range applications [1][2][3]. Furthermore, IPMSM presents enhanced mechanical robustness, compared to surface mounted PM motors, due to its particular rotor structure, where the PMs are placed in particular cavities in the iron laminations, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Interior Permanent Magnet Synchronous Motors (IPMSMs) are considered to be an advantageous option for EV applications, due to their superior nominal characteristics, including high efficiency, torque density, fault tolerant capability and a wide speed operating range [1]- [3]. Double Layer IPMSMs are highly adopted for EV applications, due to their high saliency ratio and low induced Permanent Magnet (PM) flux, enhancing their suitability for high speed operating range applications [1][2][3]. Furthermore, IPMSM presents enhanced mechanical robustness, compared to surface mounted PM motors, due to its particular rotor structure, where the PMs are placed in particular cavities in the iron laminations, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1. In [1], it has been concluded that the VI Double Layer IPMSM topology for a two operating conditions design methodology presents superior operational characteristics among Double Layer IPMSM, especially at high speed-FW operation.…”
Section: Introductionmentioning
confidence: 99%